Navigating the Digital Public Sphere: A Comprehensive Study on the Role of Social Media in Fostering Political Awareness, Engagement, and Democratic Participation in the 21st Century - Rozy Rani; Dr. Rajdeep Kaur (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
In the 21st century, social media has emerged as a powerful tool for reshaping the contours of political awareness, civic engagement, and democratic participation. Platforms such as Facebook, Twitter (now X), Instagram, and YouTube have not only revolutionized how information is produced and consumed but have also created new digital public spheres where political discourse, activism, and mobilization occur in real time (Habermas, 1989; Castells, 2012). This study critically explores the extent to which social media facilitates political awareness, especially among youth and marginalized communities, by offering access to alternative narratives, real-time updates, and interactive civic dialogues (Loader & Mercea, 2011). It investigates how these platforms enable participatory politics through hashtag movements, digital campaigns, online petitions, and live political debates—mechanisms that were previously unavailable in traditional media landscapes (Boulianne, 2015). By employing a mixed-methods approach, combining quantitative surveys and qualitative content analysis, the study examines the correlation between social media use and political consciousness, voter behavior, and issue-based activism. Special attention is paid to the role of influencers, political micro-targeting, and algorithmic personalization in shaping user engagement with political content (Tufekci, 2015; Pariser, 2011). While social media amplifies democratic engagement, the study also addresses critical concerns such as misinformation, echo chambers, and digital polarization, which threaten the integrity of informed political participation (Sunstein, 2018; Wardle & Derakhshan, 2017). The findings suggest that social media can function as a double-edged sword—empowering political participation on one hand while simultaneously posing challenges to the quality of democratic deliberation on the other. This comprehensive analysis offers valuable insights for policymakers, educators, and digital platform regulators aiming to harness the civic potential of social media while mitigating its risks. As societies continue to digitize, the responsible integration of social media into political life becomes crucial for sustaining democratic ideals and encouraging informed citizenry in the digital age.